2022
DOI: 10.1111/eci.13862
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta‐analysis on oncological radiotherapy in patients with a cardiac implantable electronic device: Prevalence and predictors of device malfunction in 3121 patients

Abstract: Background The number of patients with cardiac implantable electronic devices (CIEDs) undergoing radiotherapy (RT) for cancer treatment is growing. At present, prevalence and predictors of RT‐induced CIEDs malfunctions are not defined. Methods Systematic review and meta‐analysis conducted following the PRISMA recommendations. PubMed, Scopus and Google Scholar were searched from inception to 31/01/2022 for studies reporting RT‐induced malfunctions in CIEDs patients. Aim was to assess the prevalence of RT‐induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 59 publications
1
2
0
Order By: Relevance
“…In concordance with the only meta-analysis on CIED malfunctions, we observed relatively more malfunctions in ICDs (4/68) and CRT devices (3/16) than in PMs (2/171) [29]. Furthermore, a significant correlation between malfunction in CIEDs and maximum photon energy was almost reached in our cohort (p = 0.07), suggesting that neutron-producing energies might increase the risk of malfunction, as suggested in previous publications [29,30].…”
Section: Discussionsupporting
confidence: 92%
“…In concordance with the only meta-analysis on CIED malfunctions, we observed relatively more malfunctions in ICDs (4/68) and CRT devices (3/16) than in PMs (2/171) [29]. Furthermore, a significant correlation between malfunction in CIEDs and maximum photon energy was almost reached in our cohort (p = 0.07), suggesting that neutron-producing energies might increase the risk of malfunction, as suggested in previous publications [29,30].…”
Section: Discussionsupporting
confidence: 92%
“… 55 A systematic review identified a pooled incidence of device malfunction of 6.6% (95% CI: 5.1%-8.4%) in 3121 patients. 56 The RR of device malfunction was higher when neutron-producing energies were delivered (pooled RR: 9.98; 95% CI: 5.09-19.60) and for ICDs/CRT defibrillators compared with pacemakers or CRT pacemakers (pooled RR: 2.07; 95% CI: 1.40-3.06). Also, thrombocytopenia and neutropenia caused by cancer therapy may increase the risk of bleeding and infection, respectively.…”
Section: Implantable Cardioverter-defibrillators and Cardiac Resynchr...mentioning
confidence: 96%
“…Over the years, 2–7% of patients with CIEDS undergoing therapeutic radiation developed some kind of device malfunction. 101 , 103 , 104 The risk of malfunction is related to the location and cumulative dose of irradiation, mainly at the generator site, type of energy (proton beam more dangerous), and modes of shielding. 105 Until recently, there was wide variation in the approach to patients with CIEDS undergoing radiation therapy 106 and the EHRA document meant to set more uniform standards.…”
Section: Introductionmentioning
confidence: 99%